Finger millet RNA-seq reveals differential gene expression associated with tolerance to aluminum toxicity and provides novel genomic resources - Brhane, Haftom; Haileselassie, Teklehaimanot; Tesfaye, Kassahun; Ortiz, Rodomiro; Hammenhag, Cecilia; Abreha, Kibrom B.; Vetukuri, Ramesh R.; Geleta, Mulatu (Frontiers in Plant Science, 2022)
Eleusine coracana, finger millet, is a multipurpose crop cultivated in arid and semi-arid regions of Africa and Asia. RNA sequencing (RNA-seq) was used in this study to obtain valuable genomic resources and identify genes differentially expressed between Al-tolerant and Al-susceptible genotypes. Two groups of finger millet genotypes were used: Al-tolerant (215836, 215845, and 229722) and Al-susceptible (212462, 215804 and 238323). The analysis of the RNA-seq data resulted in 198,546 unigenes, 56.5% of which were annotated with significant hits in one or more of the following six databases: NR (48.8%), GO (29.7%), KEGG (45%), PlantTFDB (19.0%), Uniprot (49.2%), and NT (46.2%). It is noteworthy that only 288 unigenes in the NR database had significant hits against finger millet sequences suggesting that finger millet's genomic resources are scarce. The gene expression analysis revealed that 322 genes were significantly differentially expressed between the Al-tolerant and Al-susceptible genotypes, of which 40.7% were upregulated while 59.3% were downregulated in Al-tolerant genotypes. Among the significant DEGs, 54.7% were annotated in the GO database with the top hits being ATP binding (GO:0005524) and DNA binding (GO:0003677) in the molecular function GO class, and DNA integration (GO:0015074) and cell redox homeostasis in the biological process GO class. Several of the annotated DEGs were significantly enriched for their corresponding GO terms. The KEGG pathway analysis resulted in 60 DEGs that were annotated with different pathway classes, of which carbohydrate metabolism and signal transduction were the most prominent. The homologs of a number of significant DEGs have been previously reported as being associated with Al or other abiotic stress responses in various crops, including carboxypeptidase SOL1, HMA3, AP2, bZIP, C3H, and WRKY TF genes. A more detailed investigation of these and other DEGs will enable genomic-led breeding for Al tolerance in finger millet. RNA-seq data analysis also yielded 119,073 SNP markers, the majority of which had PIC values above 0.3, indicating that they are highly informative. Additionally, 3,553 SSR markers were identified, of which trinucleotide SSRs were the most prevalent. These genomic resources contribute substantially to the enrichment genomic databases for finger millet and facilitate future research on this crop.